Diagnostic accuracy of clinical tests for cam or pincer morphology in individuals with suspected FAI syndrome: a systematic review. Issue 1 (27th April 2020) - Caliesch, Rahel; Sattelmayer, Martin; Reichenbach, Stephan; Zwahlen, Marcel; Hilfiker, Roger
Abstract : Objectives: To determine the diagnostic accuracy of clinical tests for cam or pincer morphology in individuals with suspected femoroacetabular impingement (FAI) syndrome and to evaluate their clinical utility. Design: A systematic review of studies investigating the diagnostic accuracy of clinical tests for cam and pincer morphology. Data sources: PubMed, Embase, CINAHL and SPORTDiscus. Eligibility criteria for selecting studies: Studies investigating the diagnostic accuracy of clinical tests for cam, pincer or mixed morphology in symptomatic patients. Patients had to undergo an index test and a reference test able to identify cam or pincer morphology. Study results have to allow the calculation of true or false positives and/or negatives to calculate sensitivity, specificity, likelihood ratios (LR) and post-test probabilities. Results: Eight studies were included, investigating 17 tests and two test combinations. The studies reported a low specificity for all tests, ranging from 0.11 to 0.56. Sensitivity ranged from 0.11 to 1.00, with high sensitivities for the flexion-adduction-internal rotation (FADIR), foot progression angle walking (FPAW) and maximal squat tests. We estimated that negative test results on all of these three tests would result in a negative LR of 0.15. However, we judged the studies to provide low-quality evidence. Conclusion: There is low-quality evidence that negative test results reduce the post-test probability of cam or mixed morphologies and that consecutive testing with the FADIR, FPAW and maximal squat tests might be used as a clinical test combination. We would not recommend their use to confirm the diagnosis of FAI syndrome. PROSPERO registration number: CRD42018079116.